2019
DOI: 10.1002/tea.21541
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological framing and novice elementary teachers' approaches to learning and teaching engineering design

Abstract: As engineering learning experiences increasingly begin in elementary school, elementary teacher preparation programs are an important site for the study of teacher development in engineering education. In this article, we argue that the stances that novice teachers adopt toward engineering learning and knowledge are consequential for the opportunities they create for students. We present a comparative case study examining the epistemological framing dynamics of two novice urban teachers, Ana and Ben, as they l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…These discipline‐specific processes for building and communicating knowledge have been termed epistemic practices (Cunningham & Kelly, ; Sandoval & Reiser, ). Although many secondary contexts for knowledge production (Bernstein, ) do not have dedicated instructional blocks for the discipline of engineering, scholars (e.g., Wendell, Swenson, & Dalvi, ) have demonstrated that the epistemic practices of one discipline can be enacted at a task level even in instructional settings designated for other disciplines. For example, the epistemic practices of engineering can be demonstrated through individual engineering design tasks or argumentative tasks within the context of instructional blocks designated for other subjects such as science, literacy, or technology education (e.g., Wilson‐Lopez, Gregory, & Larsen, ; Wilson‐Lopez & Minichiello, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These discipline‐specific processes for building and communicating knowledge have been termed epistemic practices (Cunningham & Kelly, ; Sandoval & Reiser, ). Although many secondary contexts for knowledge production (Bernstein, ) do not have dedicated instructional blocks for the discipline of engineering, scholars (e.g., Wendell, Swenson, & Dalvi, ) have demonstrated that the epistemic practices of one discipline can be enacted at a task level even in instructional settings designated for other disciplines. For example, the epistemic practices of engineering can be demonstrated through individual engineering design tasks or argumentative tasks within the context of instructional blocks designated for other subjects such as science, literacy, or technology education (e.g., Wilson‐Lopez, Gregory, & Larsen, ; Wilson‐Lopez & Minichiello, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The widespread response of teacher educators to these challenges is to introduce PSTs to the engineering design process (EDP) as the vehicle for learning to teach engineering projects (Aydeniz and Bilican, 2018;Coppola, 2019;Lin and Williams, 2017;Mativo and Park, 2012;Radloff and Capobianco, 2019;Wendell et al 2019;Winarno et al 2020). However, most students starting primary teacher-training are unlikely to have had much exposure to engineering design at school (Dalvi et al 2020).…”
Section: Pre-service Primary Teachers' Preparation For Engineering Educationmentioning
confidence: 99%
“…Technology students may have a narrow conception of the design process, not perceiving it to be an iterative process that encourages reflection on failure and learning from mistakes (McRobbie et al 2000), so they skip the re-design stage or simply frame the project as building a product rather than being a process (Coppola, 2019;Wendell et al 2019).…”
Section: Pre-service Primary Teachers' Preparation For Engineering Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The field has started to examine these aspects of engineering pedagogy, in terms of practices and moves [3], [21]- [23]. There have been accompanying efforts to characterize pedagogical content knowledge in engineering [6], [24], [25] and how teachers' own disciplinary experiences can influence their goals for teaching [26]. Our prior work has emphasized the importance of pedagogical responsiveness, looking at what teachers with varying degrees of experience teaching engineering notice in students' thinking and how they respond [2], [27].…”
Section: Teacher Learning In Engineeringmentioning
confidence: 99%